2018
DOI: 10.1038/s41467-018-03448-w
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the role of floral sensory stimuli in pollination networks

Abstract: Despite progress in understanding pollination network structure, the functional roles of floral sensory stimuli (visual, olfactory) have never been addressed comprehensively in a community context, even though such traits are known to mediate plant–pollinator interactions. Here, we use a comprehensive dataset of floral traits and a novel dynamic data-pooling methodology to explore the impacts of floral sensory diversity on the structure of a pollination network in a Mediterranean scrubland. Our approach tracks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 93 publications
(146 reference statements)
4
100
0
1
Order By: Relevance
“…Previous studies have illustrated the importance of floral VOCs in community‐level plant–pollinator interactions, mainly in Mediterranean systems with disparate groups of pollinator taxa (Kantsa et al, ; Kantsa et al, ). Here, in a mesic montane meadow, we show that floral volatiles contributed to the nested structure but not the modular structure of forb–bee interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have illustrated the importance of floral VOCs in community‐level plant–pollinator interactions, mainly in Mediterranean systems with disparate groups of pollinator taxa (Kantsa et al, ; Kantsa et al, ). Here, in a mesic montane meadow, we show that floral volatiles contributed to the nested structure but not the modular structure of forb–bee interactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, at a broader spatial or temporal scale that would encompass several pollination syndromes and greater phylogenetic diversity, we might expect a stronger signal of floral VOCs to the modules that these broad taxonomic pairings could create. For example, although Kantsa et al () did not explicitly evaluate network‐level metrics of plant–pollinator interaction structure (e.g. modularity or nestedness) with respect to floral VOCs, they found that one group of floral VOCs—sesquiterpenes—was related to the distribution of plant–pollinator interactions (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migratory hummingbirds have significantly higher c-values, that is, a relatively high proportion of their interactions are with plant species from other modules, increasing overall network cohesiveness (Olesen et al 2007;Tylianakis et al 2010;Stouffer and Bascompte 2011) and the potential importance of indirect interactions. In highly seasonal pollination networks this role is achieved by pollinator species with long phenophases, who connected species with much more restricted activity periods (Martín González et al 2012;Kantsa et al 2018). Modular networks are expected to be highly resilient, as disturbances are less likely to spread beyond modules (Olesen et al 2007;Tylianakis et al 2010;Stouffer and Bascompte 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the study of interactions between plants and their pollinators over different seasons and years, including species whose phenophases may not fully overlap, has enabled us to explore the effect of climate, resource seasonality and species phenophases on community structure and species' roles. Besides a more accurate understanding of community structure and build up, these networks allow us to characterize more accurate the role of species and potential fluctuations over time (Martín González et al 2012;Chacoff et al 2017, Kantsa et al 2018. Similarly, the study of "meta-networks", i.e.…”
Section: Introductionmentioning
confidence: 99%